Management Of Food Security In Asean Economic Community And The Implication To Indonesia - Delfiyanti, Delfiyanti (Faculty of Law, Andalas University, 2023)
The blueprint of regional integration plan of ASEAN Economic Society 2005 involves an agenda of food security to improve of chain of value and regional participation globally by increasing production of food efficiency, infrastructure and technology improvement, quality conformation and food security with the global standards and investment encourage of agriculture in ASEAN. The roadmap of food security achievement of ASEAN economic society available in framework of ASEAN Integrated Food Security (AIFS) and Strategic Plan of Action on Food Security (SPA- FS) of 2020-2025. The achievement of implementation is important in sustain the ASEAN member-states to implement the development strategy of food supply chain in firm and powerful. The agreement consists of manual and recommendation not legally binding to implement voluntarily by the member-states to ensure the food security, nutrition upgrading and long-term farmer life in ASEAN. Domestically, it is a chance for Indonesia to cooperate on food security with the other member-states of ASEAN.